O miejsce książki w historii sztuki. Część III: Sztuka książki około 1900. W 150. rocznicę urodzin Stanisława Wyspiańskiego (Księgarnia Akademicka Publishing, 2022)
We are submitting to you a collection of articles that show Stanislaw Wyspianski’s involvement in work on the aesthetic shape of the book, i.e. the design of pages, fonts, illustrations and covers; discuss his contacts with bookbinders, publishers, printers and booksellers; and indicate his European artistic inspirations in the design of editorial forms. The importance of this pioneering work in the field of typography is also highlighted in the works of his students and imitators, including contemporaries. These original, fresh and surprising works continue to prove that the Cracovian master appeals to successive generations and has moved and continued to inspire for more than 150 years.